CREATIVE LIBRARY AS A CATALYST FOR STUDENTS' READING INTEREST IN KUNINGAN WEST JAVA - Intan Darmayanti; Erny Roesminingsih; Sri Setyowati; Amrozi Khamidi; Mohammad Syahidul Haq; Kaniati Amalia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to analyze the role of creative libraries as catalysts for students' reading interest by highlighting innovations in space design, literacy activities, and appreciation systems in two public schools in Kuningan, West Java. This study uses a qualitative descriptive approach with a multi-site case study design, involving key informants, namely librarians, teachers, and students. This study was conducted over six months of field data collection through observation, in-depth interviews, and documentation. Different from previous school literacy studies that focused solely on reading activities, this study introduces the